Gestational exposure to the great Chinese famine: early life undernutrition impact on prostatic hyperplasia in adulthood - Wang, Siyao; Zhang, Yong; Qi, Xiaoya; Xu, Xiaoyang (Frontiers in Nutrition, 2024)
Introduction: Benign prostatic hyperplasia (BPH) is a frequent illness in aged men that impacts their quality of life; early childhood exposure to famines may have long-term effects on the chance of developing BPH. The aim of this study is to investigate the relationship between early-life famine exposure and benign prostatic hyperplasia (BPH) risk in Chinese men born during 1959-1961. Methods: We used medical records from a large, comprehensive hospital to screen people born in China during the years of famine (1959–1961). Birthplaces were identified as indicators of famine exposure status. In the time window between 2017 and 2022, people born during the famine years who had prostatic ultrasonic examinations were selected, and their medical records were retrieved from the database. Univariate and multivariate logistic regression analyses investigated the relationship between famine exposure and BPH risk. Results: A total of 3009 subjects were included in this study. Patients with heavy famine exposure had older age, shorter height, lighter weight, lower cholesterol, lower uric acid (UA), lower aspartate aminotransferase (ALT), and a higher incidence of BPH than those with light famine exposure (all P<0.05). Univariate logistic regression showed that BPH was positively related to famine exposure, age, height, weight, and body mass index (BMI) but negatively related to UA (all p<0.05). Multivariate logistic regression showed that age and famine exposure were still independent risk factors (p<0.05), while UA was an independent protective factor for BPH (P<0.05). Heavy famine exposure increased the risk of BPH (adjusted OR = 1.214, 95% CI = 1.05–1.467, p = 0.045). Conclusions and recommendation: Famine and malnutrition exposure during early life may be independent risk factors for BPH in Chinese adults. This relationship provides additional evidence to support the fetal origins of adult diseases and offers clues for the pathological mechanisms of BPH.